2018
DOI: 10.1002/hbm.24016
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral preference in sequential decision‐making and its association with anxiety

Abstract: In daily life, people often make consecutive decisions before the ultimate goal is reached (i.e., sequential decision-making). However, this kind of decision-making has been largely overlooked in the literature. The current study investigated whether behavioral preference would change during sequential decisions, and the neural processes underlying the potential changes. For this purpose, we revised the classic balloon analogue risk task and recorded the electroencephalograph (EEG) signals associated with each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 131 publications
(164 reference statements)
0
12
0
Order By: Relevance
“…That is, the social frames influenced behavioral preference by modulating attentional allocation. But this hypothesis might encounter difficulties to explain why tDCS stimulation on the rTPJ did not affect individual decisions in the nonsocial framing (Gain/ Loss) task as well, since previous studies have shown that attention allocation also plays an important role in economic risk-taking (e.g., Yechiam and Hochman, 2014;Zhang and Gu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…That is, the social frames influenced behavioral preference by modulating attentional allocation. But this hypothesis might encounter difficulties to explain why tDCS stimulation on the rTPJ did not affect individual decisions in the nonsocial framing (Gain/ Loss) task as well, since previous studies have shown that attention allocation also plays an important role in economic risk-taking (e.g., Yechiam and Hochman, 2014;Zhang and Gu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These emotions and their neural network are controlled by frontal areas of the brain that are able to deactivate or reduce the activity of the areas related to emotional activation (e.g., Guendelman et al, 2017). Moreover, when human beings are anxious their perception of reality, and therefore of the disease, can vary, and it has been demonstrated that anxiety is associated with difficulties in decision making (for review, Bishop and Gagne, 2018;Zhang and Gu, 2018), but it has also been demonstrated that emotional regulation is followed by less risky decisions (Morawetz et al, 2019).…”
mentioning
confidence: 99%
“…Previous studies have shown that patients with trait anxiety show a choice preference for deck 1 or 2 in the IGT, [91] suggesting that deficits in social decision-making ability may be due to exaggeration of emotional feelings or emotion regulation deficits. [92,93] Emotional changes are associated with punishment or reward signals for the past and potential occurrence of an outcome, thus guiding long-term behavior according to the “somatic-marker hypothesis”. [85] In line with previous research reports, [94] our findings suggest that anxiety, caused by PI, can lead to impaired decision-making in terms of risk under ambiguous conditions.…”
Section: Discussionmentioning
confidence: 99%